Mast Cells, TGF-β1 and α-SMA Expression in IgA Nephropathy - Silva, G. E. B. (IOS Press, 2008)
IgA nephropathy (IgAN) is a kidney disease with a varying renal prognosis. Recently, many studies have demonstrated that renal α-smooth muscle actin (α-SMA) and transforming growth factor (TGF-β1) expression, as well interstitial mast cell infiltrates could represent a prognostic marker in several renal diseases. The aim of our study was to analyze the prognostic value of mast cell, TGF-β1 and α-SMA expression in IgAN. A survey of the medical records and renal biopsy reports of 62 patients with a diagnosis of IgAN followed-up from 1987 to 2003 was performed. The mean follow-up time was 74.7 ± 50.0 months. The immunohistochemical studies were performed using a monoclonal antibody anti-human mast cell tryptase, a polyclonal antibody anti-human TGF-β1, and a monoclonal antibody anti-human α-SMA. An unfavorable clinical course of IgAN was related to interstitial mast cell infiltrates and α-SMA expression in the tubulointerstitial area. Expression of glomerular TGF-β1 and α-SMA, and interstitial TGF-β1 is not correlated with clinical course in IgAN. In conclusion, the increased number of mast cells and higher α-SMA expression in the tubulointerstitial area may be predictive factors for the poor prognosis of patients with IgAN.